Exploring clonality and virulence gene associations in bloodstream infections using whole-genome sequencing and clinical data - Neidhöfer, Claudio; Neuenhoff, Marcel; Jozič, Robert; Atangcho, Brenda; Unsleber, Sandra; Neder, Ulrike; Grumaz, Silke; Parčina, Marijo (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Bloodstream infections (BSI) remain a significant cause of mortality worldwide.Causative pathogens are routinely identified and susceptibility tested, but only very rarely investigated for their resistance genes, virulence factors and clonality. Our aim was to gain insight into the clonality patterns of different species causing BSI and the clinical relevance of distinct virulence genes.Methods: For this study, we whole-genome sequenced over 400 randomly selected important pathogens isolated from blood cultures in our diagnostic department between 2016 and 2021.Genomic data on virulence factors, resistance genes, and clonality were cross-linked with in vitro data, and demographic and clinical information.The investigation yielded extensive and informative data on the distribution of genes implicated in BSI as well as on the clonality of isolates across various species.Associations between survival outcomes and the presence of specific genes must be interpreted with caution and conducting replication studies with larger sample sizes for each species appear mandatory. Likewise a deeper knowledge on virulence and host factors will aid the interpretation of results and might lead to more targeted therapeutic and preventive measures. Monitoring transmission dynamics more efficiently holds promise to serve as a valuable tool in preventing in particular BSI caused by nosocomial pathogens.